Building manufacturing flexibility with strategic suppliers and contingent effect of product dynamism on customer satisfaction. Issue 3 (June 2018) - Sáenz, María Jesús; Knoppen, Desiree; Tachizawa, Elcio Mondonca
Abstract: A critical capability sought by an increasing number of firms is manufacturing flexibility, because it allows to effectively respond to dynamic markets. Grounded upon a supply chain perspective, this paper aims to assess antecedents of manufacturing flexibility that stem from the upstream relationships with strategic suppliers. Additionally, it is one of the first to analyze the contingent effect of product dynamism on the impact of manufacturing flexibility on downstream customer satisfaction. We apply structural equation modeling to a sample of 155 companies in order to analyze our hypotheses. Results strongly indicate that buyer-supplier collaboration facilitates inter-organizational learning that in turn allows organizations to develop manufacturing flexibility and increase customer satisfaction. Approaching manufacturing flexibility from a broader supply chain view thus pays off. Moreover, we apply multi-group confirmatory factor analysis to explore the contingent effect of product dynamism on the relationship between manufacturing flexibility and customer satisfaction. Results suggest a stronger impact of manufacturing flexibility on performance in the context of higher product dynamism in companies' customer markets, confirming the importance of a contingency view to flexibility. Highlights: Applies SEM and MGCFA to a sample of 155 companies. Demonstrates the important role of upstream relationships for flexibility. Inter-organizational learning fully mediates collaboration on flexibility. Flexibility positively impacts downstream in customer satisfaction. Impact of flexibility on performance increases with higher product dynamism.